2009
DOI: 10.1021/jp905811t
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of ICl(CO2)nPhotodissociation: Effects of Structure, Excited State Charge Flow, and Solvent Dynamics

Abstract: Experiments on the photodissociation of ICl(-) within size-selected CO(2) clusters [Nadal, M. E.; Kleiber, P. D.; Lineberger, W. C. J. Chem. Phys. 1996, 105, 504.] differ from analogous experiments on homonuclear systems in two major ways: an early onset of caged, ICl(-)-based products with cluster size peaking at n = 5 and a rapid decline of caging after n = 5 in favor of dissociated, Cl(-)-based fragments. Using an effective Hamiltonian model for the solute electronic structure and nonadiabatic MD trajectori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…This allows the solvated system to evolve adiabatically from an initially excited state, which in the bare anion would dissociate to form I − + Cl, to generate I * + solvated Cl − products. Indeed, molecular dynamics simulations by Faeder and Parson 7 showed that following visible photoexcitation of ICl − (CO 2 ) n nearly all of the observed Cl − -based products are accompanied by I * ( 2 P 1/2 ) products as a result of dissociation to this asymptotic state. The second possible mechanism occurs on the ground-state potential for ICl − (CO 2 ) n .…”
Section: Introductionmentioning
confidence: 99%
“…This allows the solvated system to evolve adiabatically from an initially excited state, which in the bare anion would dissociate to form I − + Cl, to generate I * + solvated Cl − products. Indeed, molecular dynamics simulations by Faeder and Parson 7 showed that following visible photoexcitation of ICl − (CO 2 ) n nearly all of the observed Cl − -based products are accompanied by I * ( 2 P 1/2 ) products as a result of dissociation to this asymptotic state. The second possible mechanism occurs on the ground-state potential for ICl − (CO 2 ) n .…”
Section: Introductionmentioning
confidence: 99%
“…In Table 1 we collected examples of many different simulated processes, all involving nonadiabatic transitions: they include photon adsorption and emission [7,38,46,64,276,307], photoionization [170,211], InterSystem Crossing [155,308,309], excitation energy transfer [310], exciton dissociation [311], ultrafast decay of nucleobabses [312][313][314][315], hole or electron transfer [316][317][318][319], proton transfer [320,321], anelastic and reactive scattering [276,322], photoisomerization [116,133,179,236,237,256,320,323,324] and photodissociation [133,155,179,[325][326][327][328][329][330]. In practically all cases, excited state decay and geometrical relaxation are essential ingredients of the simulation.…”
Section: Examples Of Applicationsmentioning
confidence: 99%
“…There has been an extensive body of work over more than two decades on the interaction of dihalide anions with CO 2 , experimentally mostly performed by Lineberger and coworkers [129][130][131][132][133][134][135][136][137][138][139][140][141][142][143], with theoretical work notably done by Parson and coworkers [135,[137][138][139][140][142][143][144][145][146][147][148][149][150] and by McCoy and coworkers [137,142,143,151,152]. In this series of papers, CO 2 had the role of a solvent that could react to electronic excitation of a solvated ion and modify the solute ion's photophysics as well as its vibrational characteristics.…”
Section: Interaction Of Co 2 With Dihalide Anions -Solvent-solute Intmentioning
confidence: 99%